2024
DOI: 10.1017/s1742170523000510
|View full text |Cite
|
Sign up to set email alerts
|

Unanswered questions and unquestioned answers: the challenges of crop residue retention and weed control in Conservation Agriculture systems of southern Africa

Christian Thierfelder,
Blessing Mhlanga,
Hambulo Ngoma
et al.

Abstract: Production and utilization of crop residues as mulch and effective weed management are two central elements in the successful implementation of Conservation Agriculture (CA) systems in southern Africa. Yet, the challenges of crop residue availability for mulch or the difficulties in managing weed proliferation in CA systems are bigger than a micro-level focus on weeds and crop residues themselves. The bottlenecks are symptoms of broader systemic complications that cannot be resolved without appreciating the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…Farmers in the FGDs reported that high costs of herbicides and pesticides accelerated CA dis-adoption in the study area. Similarly, studies by Thierfelder et al (2016b) and Tsegaye et al (2017) reported that weed control was an important challenge during the early years of CA adoption and Thierfelder et al (2024) identify weeds and weed control as the Achilles heel of CA adoption and one where several questions remain unanswered and some answers unquestioned. Tufa et al (2023) report that weeding is the foremost farm operation for which farmers in southern Africa face labor shortages.…”
Section: Determinants Of Non-adoption and Dis-adoption Of Camentioning
confidence: 99%
See 1 more Smart Citation
“…Farmers in the FGDs reported that high costs of herbicides and pesticides accelerated CA dis-adoption in the study area. Similarly, studies by Thierfelder et al (2016b) and Tsegaye et al (2017) reported that weed control was an important challenge during the early years of CA adoption and Thierfelder et al (2024) identify weeds and weed control as the Achilles heel of CA adoption and one where several questions remain unanswered and some answers unquestioned. Tufa et al (2023) report that weeding is the foremost farm operation for which farmers in southern Africa face labor shortages.…”
Section: Determinants Of Non-adoption and Dis-adoption Of Camentioning
confidence: 99%
“…One key informant from TLC indicated that the provision of herbicides had been a crucial impact of the TLC CA project activities. However, Muoni et al (2014) and Thierfelder et al (2024) warn that herbicides may not be affordable for most smallholder farmers and may have undesirable effects on human health and the environment. As such, there is need to explore alternative weed control measures such as biological control (e.g., use of cover crops, microorganisms, integrated weed control) and mechanical weed control (Lee and Thierfelder, 2017).…”
Section: Determinants Of Non-adoption and Dis-adoption Of Camentioning
confidence: 99%